Financial Transition in Europe and Central Asia : Challenges of the New Decade - Bokros, Lajos (Washington, DC: World Bank, 2013)
The financial sectors of the post-communist economies of Europe and Central Asia are perhaps where the most intractable problems existed and where the most difficult reforms were forced to begin. This report examines the factors that influenced, and will influence, the adaptation of ECA's financial systems, starting from an examination of how the global financial system--especially the Western European component--has evolved, and how these developments have both influenced and challenged different types of transition economies. The report also provides an opportunity to take stock of progress in the financial systems of ECA countries over the past 10 years and to identify the main challenges confronting financial policymakers during this period.